Corporate governance and financial reporting quality in the Nigerian listed firms : the moderating effect of debt structure - Kibiya, Muhammad Umar (2016)
The quality of financial report depends on its reliability, comparability, accuracy and relevance that could guide investors make an informed investment decision.The objective of this study among others is to investigate the moderating effect of leverage on the relationship between board, and audit committee characteristics and financial reporting quality in the context of Nigerian non-financial listed firms. The study also examines the impact of changes in Nigeria’s Code of Corporate Governance, 2011 on the quality of financial reporting between 2010 and 2014. Using multiple regression technique, the study utilised McNichols (2002) measure of earnings quality using pooled panel data, with 101 sample and 505 firm-year observations. The results reveal that the relationship between leverage, audit committee share ownership, board gender diversity and audit committee financial expertise are negative and statistically significantly associated with earnings management at 5% level. This indicates that the long-term debt has a monitoring ability in mitigating earnings management practices, thus, enhancing financial reporting quality of Nigerian non-financial listed firms. This study also finds that the revised Nigerian Securities and Exchange Commission Code of Corporate Governance, 2011 has brought about new regulatory changes that effectively enhance the quality of financial reporting. The practical and the theoretical contribution of this study indicates that the agency theory and resource dependence theory are important theories when explaining corporate governance practices in Nigeria. However, further studies might extend the data collection to financial institutions, family controlled and private companies. Again, to clearly understand the inner workings of the audit committee in Nigeria, a more detail qualitative and case studies could be carried out.